The characteristics and determinants of capital structure in small businesses: empirical evidence from UK companies - Zhou, Henglei (2010)
This dissertation investigates the determinants of capital structure of small and medium sized enterprises (SMEs) in UK by use of a panel data containing 500 firms from 2001 to 2008. Different capital structure theories are reviewed in order to propose the testable hypotheses regarding the UK SMEs capital structure decisions. To test these hypotheses, the Dynamic Panel Data model and Least Square Dummy Variable are utilized. The empirical evidence indicates that SMEs differ from large companies in terms of capital structure choice due to their specific characteristics. And the pioneering capital structure theories such as trade-off, pecking order, agency and signaling theories can only partially applied to the SMEs context. The empirical evidence suggests that profitability, size, effective rate, tangibility and age have significant impacts on UK SMEs capital structure. On the contrary, growth opportunity seems to be less important to influence the capital structure decision. Furthermore, SMEs are found to have target gearing ratio and adjust towards the target at some expenses. Finally, industry and time effects are proved to have effects on the UK SMEs capital structure decisions.